Edukasi, Vaksinasi, dan Kastrasi Kucing dalam Meningkatkan Kesehatan Hewan dan Kesadaran Masyarakat di Bukittinggi: Education, Vaccination, and Cat Castration in Improving Animal Health and Community Awareness in Bukittinggi - Fadillah, Sucia; Safitri, Widia; Rahmi, Nur; Pertiwi, Sedrisa Lidya; Khanh, Varhanno Khallifhatul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Animal health plays a crucial role in maintaining ecosystem balance and preventing the spread of zoonotic diseases. In Bukittinggi, uncontrolled cat populations and the potential spread of rabies pose significant public health concerns. This community service program aimed to improve animal health and raise public awareness through education on animal care, rabies vaccination, and male cat castration. The activity was attended by 55 community participants who owned pets. A holistic approach was employed, combining medical services—vaccination and castration—with direct community education. The program successfully vaccinated 80 cats and castrated 15 male cats, while significantly increasing community knowledge, as evidenced by pre- and post-test scores (from 6.00 to 9.55). The satisfaction rate among participants reached 96%. These results demonstrated the program's effectiveness in improving animal health, reducing the risk of zoonotic diseases, and raising public awareness about responsible pet care. This model intervention could serve as an example for zoonotic disease control and enhancing animal welfare within communities.